Composite foundations on Malaysian soft clay soil: applications of innovative techniques - Mohd Yusof, Khairul Nizar (2012)
An innovative technique of electro osmosis coupled with vertical surcharge loading to accelerate the consolidation and stiffen Kaolin (China Clay Grade E) was investigated in this study. The geotechnical properties of this China Clay Kaolin Grade E and the design of electro osmotic consolidation chamber are discussed together with an explanation of the procedural concept of the electro osmotic consolidation chamber (i.e., the preparation of the apparatus and the clay sample, assembling of the electro osmotic consolidation chamber; and the experimental work). The plastic limit, liquid limit and plasticity index were 35%, 53% and 18% respectively. Therefore, China Clay Kaolin Grade E is classified as MH soil, and it is predominantly a silt with high plasticity. The specific gravity of the soil is 2.65. To ensure the kaolin is saturated, all samples were prepared in a similar manner with deaired water to produce a slurry at 150% of the liquid limit (initial moisture content of 79.5%). The electro osmotic consolidation chamber was cylindrical and consisted of the body, the base and the top cap. The body and the base of the chamber were constructed of polyvinyl chloride (PVC) tube with a wall thickness of 10.9 mm, 345 mm high and 251 mm inner diameter. The electro osmotic consolidation chamber was assembled together with a 45 mm thick flange and collar. The top cap of this chamber was based on that of a Rowe cell of similar diameter. Twenty one tests were performed in this study with an applied voltage and one test was a control test. The test samples in the twenty one tests were all consolidated to three different phases. In Phases 1 and 2, the samples were consolidated at 15 kPa while in the Phase 3, 50 kPa was used. The electro osmotic process was only performed during Phase 2. The time of treatment, numbers of electrodes, the arrangement of electrodes, and the applied voltages were investigated in these tests. Results from these tests indicated that the China Clay Kaolin Grade E in a 79.5% slurry form responded well to electro osmotic treatment and that electro osmotic process increased the overall stiffness of the soil as indicated by the reduced relative settlement in Phase 3 with a pressure of 50kPa. The water content around the anodes was less than that at the cathode creating zones of higher average constrained stiffness. The tests demonstrated that the longer the time of treatment, the greater the numbers of anodes, the shorter distance between the electrodes and the higher the applied voltages associated with electro osmosis increased the average stiffness of the soil mass confirming the concept of an electro osmotic pile. Keywords: electro osmotic merged vertical loading and electro osmotic, consolidation, electro osmotic consolidation chamber, stiffening.